KEANEKARAGAMAN ARTHROPODA PADA PERTANAMAN BAWANG MERAH DENGAN INTENSITAS APLIKASI PESTISIDA YANG BERBEDA DI KABUPATEN SIGI - Ratnawati; Kasman Jaya (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2020)
Biodiversity is an important part of the agricultural ecosystem (agroecosystem) and diversity is determined by the environment and the application of pesticides in the field. Research on the diversity of arthropods in shallot cultivation with different intensities of pesticide application aims to determine the types and populations of arthropods in shallot cultivation on land with different intensities of pesticide application. The research was conducted in the village of Soulowe, which is the center of shallot plants in Sigi Regency, with a massive and intensive application of pesticides, from December 2019 to March 2020. Sampling was carried out using absolute methods (direct observation) and relative methods (Pitffal Traf and Jaring Ayun). The results of the identification carried out in the Unisa and Untad Palu laboratories found that the diversity of arthropods in low-intensity areas of pesticide application was more than that of medium and high applications. There are 7 orders and 13 families, namely Oxyopidae, Grillotalpidae (Ordo Araneae), Scarabaeidae, Coccinellidae (Order Coleoptera), Forficuloidea (Order Dermaptera), Agromyzidae, Muscidae (Order Diptera), Formicidae, Apidae (Order of Hymenoptera), Noctuidae (Order of Hymenoptera) and Acrididae, Gryllidae andTotigonidae (Order Orthoptera). The level of diversity, evenness and family wealth as well as the abundance of arthropod individuals were higher in land with low pesticide application intensity than medium and high pesticide application.